2019
DOI: 10.1016/j.bpj.2019.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of MDCK II Cells Depends on Confluency and Cell Size

Abstract: Mechanical phenotyping of adherent cells has become a serious tool in cell biology to understand how cells respond to their environment and eventually to identify disease patterns such as the malignancy of cancer cells. In the steady state, homeostasis is of pivotal importance, and cells strive to maintain their internal stresses even in challenging environments and in response to external chemical and mechanical stimuli. However, a major problem exists in determining mechanical properties because many techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Individual MDCK-II cells show mechanoresponse in the between 0.6 to 5 kPa, while no signicant dierences were noted on 11, 20, 34 kPa [34]. That coincides with the range reported for in vivo stiness of kidneys [66,67] and stiness of MDCK-II cells themselves [68]. This range also coincides with the range at which we observe major changes in tissue organization and mechanoresponse.…”
Section: Macroscopic Organisation On Soft Gelssupporting
confidence: 89%
“…Individual MDCK-II cells show mechanoresponse in the between 0.6 to 5 kPa, while no signicant dierences were noted on 11, 20, 34 kPa [34]. That coincides with the range reported for in vivo stiness of kidneys [66,67] and stiness of MDCK-II cells themselves [68]. This range also coincides with the range at which we observe major changes in tissue organization and mechanoresponse.…”
Section: Macroscopic Organisation On Soft Gelssupporting
confidence: 89%
“…In HeLa cells, treatment with the myosin II inhibitor blebbistatin fully rescued protrusion formation of S. flexneri that produces IpaC R362W (Figures 3C and 3D) but did not affect protrusion formation by bacteria producing WT IpaC, demonstrating that protrusion formation requires IpaC-mediated reduction in membrane tension. The membrane tension of cells is inversely proportional to their density in a monolayer (Nehls et al, 2019). We therefore hypothesized that the role of IpaC R362 in protrusion formation might be more pronounced in sub-confluent cells than in confluent cells.…”
Section: Cell-cell Tension Is Reduced By S Flexneri In An Ipac-depenmentioning
confidence: 99%
“…With time, the area of growing or winner cells becomes larger than the neighbouring or loser cells (Figure 10B). Stefan et al (Nehls et al, 2019) reported that the stiffness of MDCK cells depends upon their size, i.e., big cells have high stiffness, and small cells have less stiffness. Therefore, it suggests that the winner cells of the colonies have higher stiffness compared to the loser cells.…”
Section: Discussionmentioning
confidence: 99%